The effects of sleep patterns on the college students’ nutritional status - Reyhan Ariel Maxentian Maryon; Dorna Yanti Lola Silaban (Science Midwifery, 2023)
This study aims to determine the correlation between sleep patterns and nutritional status in students of the Faculty of Medicine, Tarumanagara University. This research employed an analytical observational with a cross-sectional approach and had been permitted by Tarumanagara University. The number of samples in this study was 204 people obtained through calculations using unpaired analytic research formulas. Data were collected using a semi-quantitative food frequency questionnaire (SQ-FFQ) and a Pittsburgh sleep quality index (PSQI) questionnaire. The results of the Chi-square test showed that there was no correlation between gender (p-value = 0.79), class (p-value = 0.94), and food intake (p-value = 0.782) on nutritional status. Moreover, the results of the ANOVA test (p-value = 0.584) indicate no correlation between age and nutritional status in students of the Faculty of Medicine, Tarumanagara University. At the same time, the variable sleep pattern on food intake found a p-value = 0.000 through the Kolmogorov-Smirnov test. It means that there is a correlation between sleep patterns and food intake by these students. In addition, the Kolmogorov-Smirnov test was also carried out on the variable of sleep pattern on nutritional status with p-value = 0.000, which means there was a correlation between sleep patterns and nutritional status. In conclusion, this study indicates a correlation between sleep patterns and nutritional status in the Faculty of Medicine students at Tarumanagara University.